Simulation of the Clinical and Pathological Manifestations of Coronavirus Disease 2019 (COVID-19) in a Golden Syrian Hamster Model: Implications for Disease Pathogenesis and Transmissibility. (26th March 2020) - Chan, Jasper Fuk-Woo; Zhang, Anna Jinxia; Yuan, Shuofeng; Poon, Vincent Kwok-Man; Chan, Chris Chung-Sing; Lee, Andrew Chak-Yiu; Chan, Wan-Mui; Fan, Zhimeng; Tsoi, Hoi-Wah; Wen, Lei; Liang, Ronghui; Cao, Jianli; et al.
Abstract: Background: A physiological small-animal model that resembles COVID-19 with low mortality is lacking. Methods: Molecular docking on the binding between angiotensin-converting enzyme 2 (ACE2) of common laboratory mammals and the receptor-binding domain of the surface spike protein of SARS-CoV-2 suggested that the golden Syrian hamster is an option. Virus challenge, contact transmission, and passive immunoprophylaxis studies were performed. Serial organ tissues and blood were harvested for histopathology, viral load and titer, chemokine/cytokine level, and neutralizing antibody titer. Results: The Syrian hamster could be consistently infected by SARS-CoV-2. Maximal clinical signs of rapid breathing, weight loss, histopathological changes from the initial exudative phase of diffuse alveolar damage with extensive apoptosis to the later proliferative phase of tissue repair, airway and intestinal involvement with viral nucleocapsid protein expression, high lung viral load, and spleen and lymphoid atrophy associated with marked chemokine/cytokine activation were observed within the first week of virus challenge. The mean lung virus titer was between 10 5 and 10 7 TCID50 /g. Challenged index hamsters consistently infected naive contact hamsters housed within the same cages, resulting in similar pathology but not weight loss. All infected hamsters recovered and developed mean serum neutralizing antibody titers ≥1:427 14 days postchallenge. Immunoprophylaxis with early convalescent serum achieved significant decrease in lung viral load but not in lung pathology. No consistent nonsynonymous adaptive mutation of the spike was found in viruses isolated from the infected hamsters. Conclusions: Besides satisfying Koch's postulates, this readily available hamster model is an important tool for studying transmission, pathogenesis, treatment, and vaccination against SARS-CoV-2. Abstract : A novel, readily available, physiological small-animal model of the Syrian hamster for SARS-CoV-2 infection that recapitulates the clinical, virological, histopathological, and immunological characteristics of human disease was established to study the pathogenesis, transmission, and passive immunization effect of COVID-19.